20. EMPIRICAL ANTIBIOTIC TREATMENT FOR COMMUNITY- ACQUIRED PNEUMONIA AT CAN THO CENTRAL GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2024)
Aim: (1) Survey the empirical antibiotic therapy in community-acquired pneumonia patients hospitalized at Can Tho Central General Hospital in 2024; (2) Describe rate of clinical response status of patients after receiving empirical antibiotic therapy.Methods: Cossectional on 95 patients aged 18 years and older diagnosed with community-acquired pneumonia and receiving empirical antibiotic therapy admitted to Respiratory department at Can Tho Central General Hospital from January 2024 to April 2024.Results: In the study, there were 52 male patients, 43 female patients, average age was 73.53 ± 14.87 years old. Patients were hospitalized mainly because of sputum cough (95.8%) and fever (77.9%), crackles and dampness appeared in the majority of patients (97.9%). The rate of monotherapy with 3rd generation Cephalosporin is 20% and combined with another antibiotic group is 80%. The antibiotic group most commonly used in combination treatment is Quinolon, accounting for 96.8%. Evaluation of treatment results after 72 hours showed that 79 (83%) patients responded well, of which 62 (81.58%) received combined antibiotics.Conclusion: Empirical antibiotic treatment with 3rd generation Cephalosporin brings quite high response results, this is the first-line antibiotic group to initiate treatment of community-acquired pneumonia.
Keywords: Community-acquired pneumonia, Cephalosporin, Quinolon.